ETHNOMATHEMATICS IN CONTEXTUAL LEARNING: IMPACT ON SECONDARY STUDENTS’ MATHEMATICAL REASONING AND PROBLEM SOLVING - Febriana, Dian; Nur Hasvira Tul Aulia; Nirfayanti (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the contribution of ethnomathematics in contextual mathematics learning to the development of junior secondary students’ mathematical reasoning and problem-solving skills using a Systematic Literature Review (SLR) approach following the PRISMA 2020 framework. A total of 15 selected articles were analyzed qualitatively based on relevance, recency, and full-text availability criteria. The results indicate that ethnomathematics is implemented through the exploration of local culture, integration of mathematical concepts into real-life contexts, and the development of contextual learning media. This approach supports the development of mathematical reasoning and enhances problem-solving skills through reflective processes. Furthermore, it creates more meaningful learning experiences, increases students’ motivation, and strengthens conceptual understanding. These findings provide an empirical basis for developing innovative, contextual, and culturally relevant mathematics learning. Penelitian ini bertujuan menganalisis kontribusi etnomatematika dalam pembelajaran matematika kontekstual terhadap kemampuan penalaran dan pemecahan masalah siswa SMP melalui pendekatan Systematic Literature Review (SLR) dengan tahapan PRISMA 2020. Sebanyak 15 artikel terpilih dianalisis secara kualitatif berdasarkan kriteria relevansi, kebaruan, dan ketersediaan teks lengkap. Hasil kajian menunjukkan bahwa etnomatematika diterapkan melalui eksplorasi budaya lokal, integrasi konsep matematika dalam pengalaman nyata, serta pengembangan media kontekstual. Pendekatan ini terbukti mendukung penalaran matematis dan meningkatkan kemampuan pemecahan masalah secara reflektif. Selain itu, pembelajaran menjadi lebih bermakna, meningkatkan motivasi, serta memperkuat pemahaman konsep siswa. Temuan ini menjadi dasar pengembangan pembelajaran matematika yang inovatif, kontekstual, dan berbasis budaya lokal.